Effect of Laminate Properties on the Failure of Cross Arm Structure under Multi-Axial Load - Mohamad D.; Syamsir A.; Beddu S.; Kamal N.L.M.; Zainoodin M.M.; Razali M.F.; Abas A.; Seman S.A.H.A.; Ng F.C. (Institute of Physics Publishing, 2023)
Axial loads; Laminated composites; Manufacture; Safety engineering; Structural properties; Three dimensional computer graphics; ITS applications; Laminate configuration; Laminate damage; Laminate properties; Mechanical deformation; Quasi-static loading; Three dimensional finite element model; Ultimate stress; Failure (mechanical)